IMPLEMENTASI PASAL 2 AYAT (1) UNDANG-UNDANG NO. 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG SEBAGAI SYARAT PENGAJUAN PERMOHONAN PAILIT (ANALISA YURIDIS ATAS PUTUSAN PENGADILAN DALAM PERKARA KEPAILITAN PT. CIPTA TELEVISI PENDIDIKAN INDONESIA) - , Dwi Laksono Setyowibowo, SH, Prof. Dr. Nindyo Pramono, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study focused on analyzing the implementation of bankrupcy requirements stipulated in Article 1 paragraph (2) of Law No.37 Year 2004 regarding Bankrupcy and Suspension and Debt Settlement Obligation (âBankrupcy and PKPU Lawâ) in conjunction with Article 8 paragraph (4) of Bankruptcy and PKPU Law regarding the existence of simple authentication in debts, particularly in the bankrupcy case of PT. Cipta Televisi Pendidikan Indonesia (âPT. TPIâ). Besides, this study is also focused on debts settlement through bankruptcy mechanism directly in Commercial Court without prior to settle the case through lawsuit mechanism in District Court. The aims of the study includes an analyzing the implementation of bankrupcy requirements in connection with simple authentication to the debts existence on the bankrupcy case of PT. TPI